(untitled) (American Journal of Islam and Society, 1997)
The last centuries of human history bear witness to the generation of havoc and carnage brought about by the disintegration of world empires and superpowers that ruled vast areas inhabited by people of different ethnic. religious, and national backgrounds. One such event took place in the early period of this century: the collapse of the Ottoman Empire. Its downfall left a power vacuum in many areas of the Balkans. North Africa and the Middle East. Out of the ashes of its ruin, new and independent states emerged. Toward the end of the twentieth century, the Soviet Union totally disintegrated and suddenly disappeared from the international scene in a relatively short time. As mentioned. history has recorded the gradual decline and final fall of great empires. The collapse of the Soviet Union differs from other older empires. We will draw a comparison between its disintegration and the fall of the older Ottoman Empire. There are abundant scholarly and literary analyses indicating that the Ottoman Empire underwent a process of gradual dismantling from it initial decline to its final collapse. The Soviet Union, however, underwent an abrupt end to its reign and. entered ultimate oblivion without experiencing a prolonged loss of vitality. This abrupt fall and quick end may be auributed to various factors, from the failure of economic policies to the yearning for freedom. including the revival of ethnic, religious. and national identities. These are the points emphasized by Swietochowski’s timely book on Russia and Azerbaijan. The current wave of world events exerts itself nor only upon the political elite but also within academic quarters and on publishing trends. As the 1979 Iranian revolution drew greater attention to Islam and was followed by the establishment of new departments of Islamic studies and the publication of hundreds of books on the subject, the collapse of the Soviet Union generated a significant amount of interest and, accordingly, academicians and publishing houses responded to the growing search to know more about the region. Swietochowski’s look should be considered a significant contribution to these effons. It is a widely held observation thal the disintegration of Lhe Soviet Union dramatically changed and traumatized the geopolitical and geocullural landscape of the area. Swietochowski’s book concentrates specifically on Azerbaijan by examining closely the last two centuries of this unknown land’s history. As the title Russia and Azerbaijan: A Borderland in Transition suggests, the author deals with a people whose land is divided between north and south. He uses archival sources, official documents, and numerous books and articles written in various languages to inform readers about a land and a people about which little was known before the Soviet Union’s downfall. Swietochowski’s work ...